“ALEXA, CAN I TRUST YOU?”: SMALL SISTERS AND FRIENDLY POWER - Munn, Luke (AoIR Selected Papers of Internet Research, 2019)
How is trust fabricated today? This paper argues that the persona of ‘Alexa’ bypasses concerns around surveillance and privacy, defusing anxieties not via the rationality of a convincing argument but through the relationality of Alexa as a singular presence. In many respects Alexa is actually more invasive than other technologies. Amazon has encroached into the very heart of the home. Moreover, the company’s patents delve further into the subject through voice identification, mood monitoring, and health detection. But this encroachment is carried out by her, rather than it, a warm and welcoming persona. The team’s aim is to develop something that is friendly, can turn off your lights, chat about anything, and empathize when you’re having a bad day (McGirt 2018). The goal is to construct something chattier, more affective and emotionally attuned. In doing so, Alexa embodies what theorist Byung-Chul Han (2017) has called “friendly power.” The result is that Alexa feels different. Instead of an algorithmic bundle of technologies, Alexa is experienced as an affective persona. Alexa thus delves deeper into the inner life of the subject while shrugging off the anxieties associated with cold, command-and-control technologies. Rather than an all-seeing eye, she is an always listening voice, a friendly companion. And rather than emanating from a central agency, she is co-located with the user. If Big Brother no longer characterizes contemporary power (Harcourt 2015), Alexa might be described as a “small sister.” Small sisters work alongside instead of above. Small sisters are multiple, sited, and supple.